By moving -4 to the right hand side, we get
![\begin{gathered} |12-3x|=11+4 \\ |12-3x|=15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qoxoojg1syqc2pzumolaiodijkk5lv59y5.png)
Now, by the properties of the absolute values, this last equation becomes in 2 conditions:
![\begin{gathered} a)\text{ 12-3x=15} \\ b)12-3x=-15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/gyrs6g82x2yoklzob4mhkborkxtlzbjwe1.png)
From condition a), by moving 12 to the right hand side, we get
![\begin{gathered} -3x=15-12 \\ -3x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sutrkf18xja605xdqf7z037ddvdmphvnm2.png)
and x is given by
![\begin{gathered} x=(3)/(-3) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/s8bt2fo8qjjqpfuw05d4f9zh8aua12xfb0.png)
Now, from condition b), by moving 12 to the right hand side, we have
![\begin{gathered} -3x=-15-12 \\ -3x=-27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lbm5dvpg567uw7njq126tks3lt4qfugjam.png)
then, x is given by
![\begin{gathered} x=(-27)/(-3) \\ x=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ynlzf7f7ulv755ti9negpaskepqv1rywua.png)
Therefore, the answer is the union of both solution, that is, the answer is the third option: x=-1, 9